Young children encountering death: epistemic emotions at the Hô Chí Minh Mausoleum - Dresler E (Taylor and Francis Group, United Kingdom, 2025)
Understanding death presents a significant challenge for young children, as it is a complex and multifaceted concept. The Hô Chí Minh Mausoleum in Hanoi, Vietnam, serves as a culturally significant tourism site and provides a valuable context for examining how young children engage with death. Drawing on in–depth interviews with parents, this study analyses parent–child conversations about death to explore how such interactions may influence children’s emotional responses and developing understanding of death. Thematic analysis of these conversations identified six interrelated epistemic emotions: awe, surprise, excitement, interest, curiosity, and confusion. These epistemic emotions often arise when children encounter unexpected or ambiguous information that challenges their existing experiences and understandings. This study highlights the ways in which parent–child conversations support the co–construction of new understandings by introducing children to historical narratives and cultural traditions, and by guiding their interpretation of death within broader socio-cultural contexts.